ALAT PENDETEKSI NOMINAL DAN KEASLIAN MATA UANG KERTAS - Kuswandhie, Rakhmad (Jurnal Teknologi Informasi MURA, 2015)
In the conventional process of buying and selling there will be a meeting between several people who act as sellers and buyers. But with current technology developments then the process of buying and selling can also be done without a direct meeting between the seller da. Besides buying and selling process also is not always the case between man and man, but already possible to do with an intermediary tool.Tools used in this transaction should be able to detect the nominal and the authenticity of money to support the process of buying and selling. For that to know the characteristics  and traits of each currency. In addition to the tool can work automatically then need to be prepared  several electronic  circuits  which include  optocoupler  circuits and  other  support  circuits.  As  for  the  introduction  of  nominal  and  authenticity  of  the money it can use image capture devices such as cameras and then that image will be processed with the help of software that will detect the nominal value and authenticity of banknotes.With a combination of software and hardware is expected to generate a nominal detection  tools  and  authenticity  of paper  money  that  can  work  automatically  with  the computer base